Flow boiling heat transfer on a Carbon/Carbon surface. (June 2017) - Doretti, Luca; Longo, Giovanni A.; Mancin, Simone; Righetti, Giulia; Zilio, Claudio
Highlights: The Carbon/Carbon (C/C) composite material is suggested for flow boiling heat transfer applications. The flow boiling heat transfer of R134a over a C/C surface is studied. The hysteresis of the boiling process on C/C is presented and discussed. The dewetting/rewetting process during the dryout phenomenon is presented. The two-phase flow visualizations permit to analyze in details the boiling process. Abstract: Carbon/Carbon (C/C) is one of the most high-tech materials developed by the aerospace industry and then applied to critical components in several different applications. This composite material appears to be a viable option for future thermal management devices because it exploits interesting properties having a low density and a relatively high thermal conductivity as compared to copper; moreover, it has already been used in many industrial applications where it is shaped in various forms even complex. This study explores C/C heat transfer capabilities during the boiling process of a synthetic refrigerant. In particular, this paper presents the experimental measurements carried out during flow boiling heat transfer of R134a on a C/C surface. The sample was tested in a new experimental facility especially designed for studying the flow boiling heat transfer process on innovative materials and enhanced micro- and nano-structured surfaces. The tests were run at constant mean saturation temperature of 30 °C, by varying the heat flux from 50 kW m −2 to 100 kW m −2, and the refrigerant mass velocity from 50 to 200 kg m −2  s −1 . The heat transfer measurements were compared with flow visualizations of boiling heat transfer at different operating conditions. Finally, a new model was developed and validated to estimate the refrigerant flow boiling heat transfer coefficients on C/C surface.